The pilgrimage - Coelho, Paulo (Thorsons, 2015)
On a legendary road across Spain, travelled by pilgrims of San Tiago, we find Paulo Coelho on a contemporary quest for ancient wisdom. This journey becomes a truly initiatory experience, and Paulo Coelho is transformed forever as he learns to understand the nature of truth through the simplicity of life. 'The Pilgrimage' has a very important place in the work of Paulo Coelho, not just because it is the first of his major books, after which came 'The Alchemist', but because of the complete way in which it expresses the humanity of his philosophy and the depth of his search. Paulo Coelho's visionary blend of mysticism, magical realism and folklore makes this an adventure story with a difference.